Factors Influencing Customer Loyalty Among Optical Clinics in The City of Koronadal, South Cotabato, Philippines - Jayson Diaz; Ray Lorenzo; Corine Mag-aso; Bai Sarah Akilan (Universitas Dinamika, 2023)
This paper investigates customer loyalty factors in Koronadal's optical clinic industry. It aims to provide insights for enhancing customer service and loyalty. Key factors identified in past studies include service quality, customer satisfaction, trust, and brand image. Using a quantitative approach with a descriptive-multivariate correlational design (predictive analysis), this study collects primary data through purposive-convenient sampling. Statistical results confirm that customer satisfaction and brand image significantly influence customer loyalty in the optical clinic industry, accounting for 46.7% of the loyalty variance. However, this study also revealed significant findings specific to this industry. Researchers observed that customer satisfaction and brand image played crucial roles in influencing customer loyalty in these clinics. Surprisingly, neither service quality nor customer trust exhibited a statistically significant impact on customer loyalty.These findings have important implications, stressing businesses' need to prioritize customer satisfaction and brand image to enhance loyalty, particularly given the pandemic's impact.